(untitled) (CIPEEX, 2022)
THE PRESENT WORK REPORTS IN PHOTOS FORM THE EXPERIENCE EXPERIENCED BY 13 ACADEMICS OF THE DENTISTRY COURSE - UNIEVANGLICA, MEMBERS OF THE ACADEMIC LEAGUE OF ENDODONTICS. THE MAIN OBJECTIVE OF THE VISIT WAS TO GUIDE THE HIV VIRUS PATIENTS RESIDING IN THE BETHNIA HOST HOUSE ON THE TECHNIQUES OF ORAL HYGIENE, DENTAL FLOSSING, PROSTHESIS HYGIENE AND THE MAIN LESIONS AFFECTING THE ORAL CAVITY OF SEROPOSITIVES. AS A METHODOLOGY WAS GIVEN TO A TOTAL OF 30 PEOPLE AN EDUCATIONAL / PREVENTIVE SPEECH, DIVIDED INTO TWO MOMENTS, WAS INITIALLY APPROACHED ABOUT ORAL HYGIENE WITH THE USE OF MACRO MODELS FOR DEMONSTRATIONS AND SECONDLY ON THE ORAL MANIFESTATIONS SHOWN IN A BANNER AND EXPLAINED IN DETAIL. THE RESULTS WERE SATISFACTORY, SINCE THERE WAS INTENSE PARTICIPATION AND INTERACTION BETWEEN THE STUDENTS AND PARTICIPANTS, WHICH RAISED MANY DOUBTS AND SHOWED INTEREST IN THE SUBJECT. THIS PROJECT WAS OF GREAT RELEVANCE FOR THE STUDENTS, WHO WERE ABLE TO WITNESS A DIFFERENT REALITY OF THE ACADEMIC DAY-TO-DAY AND OBTAINED PERSONAL AND PROFESSIONAL GROWTH. ON THE DAY OF THE EVENT, WE EXPOSE IN DOOR PORTRAITS MOMENTS OF THE VISIT IN THE HOST HOUSE.